Assessing treaty performance in China : trade and human rights - Potter, Pitman B. (Asia Pacific legal culture and globalization (Series), 2014)
"Closer and more frequent contact among states brought about by globalization has led to an increase in trade and human rights disputes that can challenge economic relations and cloud political relationships. Preventing and managing these disputes requires a better understanding of the cross-cultural dimensions of treaty performance on trade and human rights, especially for increasingly important actors in the international system such as China. Assessing Treaty Performance in China outlines a new approach for understanding China's treaty performance around international standards on trade and human rights, using the paradigms of selective adaptation and institutional capacity. Selective adaptation reveals how local interpretation and implementation of international treaty standards are affected by normative perspectives derived from perception, complementarity, and legitimacy. Institutional capacity explains how operational dimensions of legal performance are affected by structural and relational dynamics of institutional purpose, location, orientation, and cohesion. The book focuses on legal performance rather than technical compliance to provide a more comprehensive perspective on China's interaction with international treaty standards. It also offers policy suggestions for more effective engagement with China on trade and human rights issues"--Unedited summary from book cover